Widespread air pollutants of the North China Plain during the Asian summer monsoon season: a case study - Wu, Jiarui; Bei, Naifang; Li, Xia; Cao, Junji; Feng, Tian; Wang, Yichen; Tie, Xuexi; Li, Guohui (Atmospheric chemistry and physics, 2018)
During the Asian summer monsoon season, prevailing southeasterly–southwesterly winds are subject to delivering air pollutants from the North China Plain (NCP) to northeast and northwest China. In the present study, the WRF-CHEM model is used to evaluate contributions of trans-boundary transport of NCP emissions to the air quality in northeast and northwest China during a persistent air pollution episode from 22 to 28 May 2015. The WRF-CHEM model generally performs well in capturing the observed temporal variation and spatial distribution of fine particulate matter (PM2.5), ozone (O3), and NO2. The simulated temporal variation of aerosol species is also in good agreement with measurements in Beijing during the episode. Model simulations show that NCP emissions contribute substantially to the PM2.5 level in Liaoning and Shanxi provinces, the adjacent downwind areas of the NCP, with an average of 24.2 and 13.9 µg m−3 during the episode, respectively. The PM2.5 contributions in Jilin and Shaanxi provinces are also appreciable, with an average of 9.6 and 6.5 µg m−3, respectively. The average percentage contributions of NCP emissions to the PM2.5 level in Liaoning, Jilin, Shanxi, and Shaanxi provinces are 40.6, 27.5, 32.2, and 20.9 %, respectively. The NCP emissions contribute remarkably to the O3 level in Liaoning province, with an average of 46.5 µg m−3, varying from 23.9 to 69.5 µg m−3. The O3 level in Shanxi province is also influenced considerably by NCP emissions, with an average contribution of 35.1 µg m−3. The O3 level in Shanxi province is also influenced considerably by NCP emissions, with an average contribution of 35.1 µg m−3. The average O3 contributions of NCP emissions to Jilin and Shaanxi provinces are 28.7 and 20.7 µg m−3, respectively. The average percentage contributions of NCP emissions to the afternoon O3 level in Liaoning, Jilin, Shanxi, and Shaanxi provinces are 27.4, 19.5, 21.2, and 15.8 %, respectively. However, the effect of NCP emissions on the air quality in Inner Mongolia is generally insignificant. Therefore, effective mitigation of NCP emissions not only improves the local air quality, but is also beneficial to the air quality in northeast and northwest China during the Asian summer monsoon season.